2016
DOI: 10.1016/j.aott.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative ability of calcaneal quantitative ultrasound compared with dual-energy X-ray absorptiometry in men with hip or distal forearm fractures

Abstract: ObjectivesThe aim of this case–control study was to compare the discriminatory ability of bone mineral density (BMD) measurements and calcaneal quantitative ultrasound (QUS) parameters for fractures and to determine fracture thresholds for each variable in men with hip or distal forearm fractures.Patients and methodsA total of 20 men with hip and 18 men with distal forearm fractures and 38 age-matched controls were included in this study. Dual-energy X-ray absorptiometry (DXA) BMD (spine and hip) and calcaneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…According to the included studies, the average sample was constituted by 174 participants, with a mean age of 75 years, ranging from 50 to 89 years. Overall, the participants were people with osteoporotic fractures, osteoporotic fracture risk, and postmenopausal women [ 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the included studies, the average sample was constituted by 174 participants, with a mean age of 75 years, ranging from 50 to 89 years. Overall, the participants were people with osteoporotic fractures, osteoporotic fracture risk, and postmenopausal women [ 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In every study, the patients were distributed equally and randomly into different groups, with no significant differences. Thus, three of the ten studies used a comparison control group of healthy elderly people [ 30 , 33 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews and meta-analyses as well as the International Society for Clinical Densitometry (ISCD) validated QUS as being a good predictor for hip and other non-vertebral fractures and as reliable as DXA ( Marín et al, 2006 ; Moayyeri et al, 2012 ; Krieg et al, 2008 ). QUS is an independent predictor of fracture in men and women, even after adjusting for DXA ( McCloskey et al, 2015 ), and showed the same area under the curve as DXA in calculating the risk for fracture ( Esmaeilzadeh et al, 2016 ; Cesme, Esmaeilzadeh & Oral, 2016 ). Direct correlations between QUS and DXA showed a sensitivity of 70–85% and a specificity of 44–70% for detecting osteoporosis, and is therefore used as an estimated bone mineral density measurement (accuracy is not reported in these studies) ( Liu et al, 2019 ; Lee, Roh & Yoon, 2003 ).…”
Section: Introductionmentioning
confidence: 90%
“…If such cancellous bone is frangible, then it will often cause osteoporosis. We used an ultrasound bone densitometer because it has no side effects and correlates well with the DXA-measured BMD 23 , 24 or bone mineral contents (BMC) 23 . The densitometer was operated by one researcher experienced in taking such measurements.…”
Section: Methodsmentioning
confidence: 99%